Comparison of sugar acid neutralizing effect among five different toothpastes - Bahrudin, Adlin Farahani; Abdul Hadi, Roqaia; Wan Azmi, Wan Nur Amni; Ardini, Yunita Dewi; Hassan, Haszelini; Kharuddin, Azrul Fazwan (2018)
Introduction: Toothpastes contain bicarbonate ions that can buffer and counter the attack of acid, thus leads to remineralization. This study aims to compare the sugar acid neutralizing effect among five different toothpastes. Methodology: A cross-sectional study was conducted among undergraduate students of Kulliyyah of Dentistry, IIUM Kuantan with total samples of 57 after inclusion and exclusion criteria. Subjects were instructed to refrain from overnight oral hygiene procedure. The baseline salivary and plaque pH were recorded. The salivary and plaque pH after rinsing with cokes were measured, and the subjects were instructed to brush using assigned toothpaste based on their toothpaste groups. All the pre-brushing, post-coke and post-brushing measurements were compared between the five groups. Salivary pH was measured using portable pH meter while plaque pH was measured using pH strip method. Data was analysed by using SPSS and Amos® with significance level was set at p< 0.05. IREC approval was obtained (ID: IREC 673). Results: There was significant difference in terms of the mean pH after brushing for saliva (p=0.044 < 0.05) among the five groups, however there was no statistically significant difference for the plaque reading (p > 0.05). The toothpaste showing the highest pH after brushing is TO-1 toothpaste. Conclusions: The five brands of toothpastes possessed sugar acid neutralizing effect to a certain degree based on the saliva reading.